Determinan Perilaku Penggunaan Dompet Digital Secara Berkelanjutan oleh Mahasiswa Akuntansi - Sriniyati; Erlinda Nur Khasanah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
One of the uses of technology in the field of financial services in this era is the emergence of financial technology in the form of digital wallets (e-wallets). The use of this digital wallet is considered practical, efficient, effective and facilitates mobility, especially for the younger generation (students). The results of previous research regarding the behavioral determinants of sustainable use of digital wallets showed inconsistencies. The purpose of this study was to examine the determinants of accounting student’s e-wallet continuance usage behavior. The determinants consisted of facilitating conditions, habit, and behavioral intention. Data used in this research was primary data collected by distributing questionnaires through 100 students at Vocational Colleges in Special Region of Yogyakarta. To test the hypotheses, this study used multiple regression analysis through the IBM SPSS Statistics 26. The results of this research provide empirical evidence that all hypotheses in this research are supported. The determinants tested include facilitating conditions (sig. 0,004), habit (sig. 0,000), and behavioral intention (sig. 0,001) had a positive and significant effects on e-wallet’s continuance usage behavior by accounting students.